Impact of photovoltaic grid-tied systems on national grid power factor in Palestine - Amer Braik; Asaad Makhalfih; Ag Sufiyan Abd Hamid; Kamaruzzaman Sopian; Adnan Ibrahim (AIMS Press, 2022)
Residential photovoltaic systems are a cost-effective solution for Palestinians to reduce their power costs while improving the environment. Despite their numerous advantages, these systems have several negative effects on the entire electric grid infrastructure. Increased penetration of photovoltaic (PV) systems, for example, may result in a fall in the power factor of the distribution grid. When the power factor is low, heat production and switch failures are more likely to occur. Even though comparable research has been published in the past, this is the first time PV systems have been investigated in terms of power factors in Palestine. This research serves as a resource for people interested in how photovoltaics (PVs) impact their systems' total power factor. To begin, the researchers in this study presented an intuitive power factor selection criterion for photovoltaic (PV) systems. Second, the article included a proposal for an auxiliary power factor controller. This article's conclusions may be utilized by municipalities, grid operators, and legislators to aid them in planning, forecasting, and accommodating new PV systems in their grids in terms of total power factor, as demonstrated by the results of this study. However, even though the data in this study is drawn from Palestinian sources, it may be applied to other regions because the data sets used are worldwide in scope.